Urban Functions, Processes and Social Morphology of Amarkantak Town, Madhya Pradesh - Prasad, Janki (National Geographical Journal of India, 2022)
Towns are the places of manifold functions and these functions are mostly related to the economic and social development of urban areas. Amarkantak town is a prominent historio-religious place of Central India which is located on lush green covered Maikal hills. The topographical configuration of Amarkantak is uneven and the town is situated around the origin point of the sacred river Narmada. The temples, kunds, ponds, ashrams, and commercial shops are the foremost features of Amarkantak. The functions of Amarkantak town are widely influenced by the pilgrimage. The town has its importance as service centre in the peripheral villages and is connected with other, various important places. The process of urbanization and urban sprawl of Amarkantak are largely controlled by the religio-political factors. The segregated occupancy pattern of different ethnic groups in the town clearly shows the rural attribute of the town and its inclination towards the hierarchy based community system and religious aspect. The present study is an attempt to analyse and describe the urban functions, processes and social morphology of the settlement in spatio-cultural context